Panorama de los estudios sobre orden de palabras en latín (Minerva. Revista de Filología Clásica, 2019)
This paper describes some of the most relevant studies on Latin word order throughout our century from the descriptive, typological and functional perspective. Some of the results of the research by using these linguistic methods are analysed; the author also offers global conclusions about the achievements obtained by previous studies, and puts forward one approach which could offer a more accurate description and a more exact explanation of linguistic data.